2023
DOI: 10.1097/ta.0000000000003954
|View full text |Cite
|
Sign up to set email alerts
|

Is severe traumatic brain injury no longer a contraindication for surgical stabilization of rib fractures in patients with multiple rib fractures? A propensity-matched analysis

Abstract: BACKGROUND:Traumatic brain injury (TBI) is often considered a contraindication to surgical stabilization of rib fractures (SSRF). In this study, we hypothesized that, compared with nonoperative management, SSRF is associated with improved outcomes in TBI patients. METHODS:Using the American College of Surgeons Trauma Quality Improvement Program 2016-2019, we performed a retrospective analysis of patients with concurrent TBI and multiple rib fractures. Following propensity score matching, we compared patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Still, recent studies have challenged the role of TBI as a historical contraindication for SSRF, showing the potential benefit of chest wall stabilization in patients with TBI. 15,16,41 Namely, Prins et al reported that in patients with multiple rib fractures and TBI, SSRF was associated with decreased 30-day mortality and lower rates of pneumonia compared with nonoperative treatment. 15 However, while the timing of other surgical procedures in TBI patients has already been investigated-in patients with concurrent TBI and major orthopedic fractures Giannoudis et al 42 recommend early stabilization, as long as hypotension is avoided-no study has investigated the impact of timing to SSRF in this select patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, recent studies have challenged the role of TBI as a historical contraindication for SSRF, showing the potential benefit of chest wall stabilization in patients with TBI. 15,16,41 Namely, Prins et al reported that in patients with multiple rib fractures and TBI, SSRF was associated with decreased 30-day mortality and lower rates of pneumonia compared with nonoperative treatment. 15 However, while the timing of other surgical procedures in TBI patients has already been investigated-in patients with concurrent TBI and major orthopedic fractures Giannoudis et al 42 recommend early stabilization, as long as hypotension is avoided-no study has investigated the impact of timing to SSRF in this select patient population.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with concomitant TBI and severe chest injury have prolonged lengths of stay in the ICU, an increased need for mechanical ventilation, 1,11 and a greater risk of pneumonia and mortality. 12,13 While flail chest remains the main indication for operative rib fixation, several recent studies have shown that SSRF could be beneficial in non-flail chest injury patterns, 10 in patients with associated pulmonary contusion, 14 and in patients with concomitant TBI, 15,16 expanding the indication of this surgical practice. Among all patients requiring SSRF, early operative fixation has been associated with decreased hospital LOS, ICU LOS, and duration of mechanical ventilation; [17][18][19][20][21] and current clinical guidelines [22][23][24] promote the operative management of chest wall injuries within the first 72 hours after admission.…”
mentioning
confidence: 99%